2016
DOI: 10.1249/mss.0000000000000933
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Consumer-Based Physical Activity Monitors for Specific Activity Types

Abstract: Consumer-based PA monitors should be used cautiously for estimating EE, although they provide accurate measures of steps for structured ambulatory activity, similar to validated pedometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(144 citation statements)
references
References 29 publications
8
131
3
1
Order By: Relevance
“…This study only assessed the total measurement values for steps, EE, and active minutes over the observed period for all monitors assessed, and therefore time-matched analyses for each activity performed are not provided in current results. However, this analysis can be found in a similar study from our laboratory 15. The current study defined a step as lifting the entire foot and then placing it on the ground, which may not be the same method as the PA monitors use to recognise a step.…”
Section: Discussionmentioning
confidence: 95%
“…This study only assessed the total measurement values for steps, EE, and active minutes over the observed period for all monitors assessed, and therefore time-matched analyses for each activity performed are not provided in current results. However, this analysis can be found in a similar study from our laboratory 15. The current study defined a step as lifting the entire foot and then placing it on the ground, which may not be the same method as the PA monitors use to recognise a step.…”
Section: Discussionmentioning
confidence: 95%
“…Accelerometry showed higher error particularly during low intensity activities and cycling (99, 105, 106). In order to overcome this limitation, Bonomi et al (107) demonstrated that the AEE estimate via accelerometry can be improved if it is combined with detection of the type of activity.…”
Section: Assessment Of Energy Expenditure In Subjects With Dmmentioning
confidence: 99%
“…Our observations regarding varying HR data echo findings from a recent study by Nelson et al (2016) who examined the accuracy of various FitBit and Jawbone devices for 45 46 estimating energy expenditure (EE) and step counts. They found that consumer based 45 fitbit.com 46 jawbone.com/up physical activity monitors should be used cautiously for estimating EE, although they provide accurate measures of steps for structured ambulatory activity.…”
Section: Discussionsupporting
confidence: 82%